Benefit sharing from whale shark tourism in Botubarani, Gorontalo and Labuhan Jambu, Teluk Saleh. Issue 1 (May 2021) - Djunaidi, A; Jompa, J; Nadiarti, N; Bahar, A; Tilahunga, S D
Abstract: Whale shark tourism is a growing industry in the world. This study aimed to determine the benefits local people earn from whale shark tourism at two sites in Indonesia, Botubarani in Gorontalo Province and Labuhan Jambu, Teluk Saleh, Nusa Tenggara Barat Province. This study involved dive centres, fishermen, community tourism groups, village enterprises (BUMDES), home stay owners, car rental companies, boat owners, lift net owners, snorkelling equipment rental businesses and ecotourism operators. In Botubarani, dive centres sold whale shark watching dive trips for US42.3/pax, and snorkelling trips for US23/pax, of which, US4.6 and US2.7 went to the Pokdarwis, and US33.5 to the dive centre. For nondivers, trips cost US11.5, of which US1.5 was for whale shark bait, US1.5 went to the Pokdarwis, and US4.6 to fishermen. Whale shark watchers in Labuhan Jambu paid US211.5-US270 to ecotourism operators plus US7.7/pax to the BUMDES. From that money, US119 was paid to lift net owners, US42 to boat operators, and US19.2-US76.9 to ecotourism operators. On average, car rental companies received US46.1, home stays received US7.6, and US11.5 was paid for rental equipment.